Metacognitive Therapy for Individuals at High Risk of Developing Psychosis: A Pilot Study - Parker, Sophie Kate; Mulligan, Lee D.; Milner, Philip; Bowe, Samantha; Palmier-Claus, Jasper E. (Frontiers in Psychology, 2020)
Developing effective interventions for preventing first episode psychosis have been an important research focus in the last decade. Cognitive behavioral therapy is a currently indicated treatment for people at ultra-high risk of psychosis, however, access and resource issues limit its delivery within the NHS. Treatments which partial out potential active ingredients and are aimed at a range of psychological difficulties seen within this population have the potential to be more efficacious and efficient. We conducted a single-arm exploratory pilot trial, designed to investigate the feasibility and acceptability of Metacognitive therapy for individuals at ultra-high risk (UHR) of developing psychosis. Trial uptake was good, with 11 out of 12 referred individuals meeting for an eligibility assessment (one individual was excluded prior to the assessment). Of these, 10 individuals were eligible and included in the trial. Retention to treatment was high with 80% treatment adherence gained and an overall average of 8 sessions completed. All participants were offered follow-up assessments immediately post-treatment and at 6 months, which comprised measures of psychotic like experiences, anxiety and depression, and metacognitive processes implicated in the model. Retention to the post-treatment (12-week) follow-up was good, with 80% completion; however retention to the 6-month follow-up was lower at 60%. Clinically significant results were observed in psychotic like experiences, anxiety, depression and functioning with medium to large effect sizes. Measures related to beliefs and processes targeted within MCT showed clinically significant change with medium to large effect sizes. Our results suggest that MCT based upon a specific metacognitive model for individuals meeting ARMS criteria may be an important treatment target and warrants further attention. Limitations and possible focuses for future research are discussed. Registration: ISRCTN53190465 http://www.isrctn.com/ISRCTN53190465.